PERAN SERTIFIKAT TANAH DALAM MENINGKATKAN AKSES PEMBIAYAAN SYARIAH BAGI UMKM - Nabila Zahrotul Ula; Muhammad Rafi Aliffari; Sifa Aulia; Sofiah Sofiah (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Micro, Small, and Medium Enterprises (MSMEs) constitute a key pillar of Indonesia's economy. However, they continue to face challenges in accessing formal financing, particularly from Islamic financial institutions. One of the main obstacles to optimizing such financing is the underutilization of land certificates as legally recognized collateral. This conceptual article aims to analyze the role of land certificates in expanding MSMEs' access to Islamic financing and to examine their contribution to strengthening Islamic entrepreneurship. The study employed a library research approach through the stages of identification, selection, critical analysis, and synthesis of literature related to Islamic economics, land law, Islamic financing, and Islamic entrepreneurship. The findings indicate that land certificates serve as valid collateral (rahn) under both Islamic principles and positive law, thereby enhancing the confidence of Islamic financial institutions, expanding MSMEs' access to financing, and promoting more trustworthy, transparent, and accountable business governance. Furthermore, this study highlights that the integration of asset legality, Islamic financing, and Islamic entrepreneurship provides a conceptual foundation for strengthening Islamic financial inclusion and empowering MSMEs. The novelty of this article lies in the conceptual integration of land certificates, Islamic financing, and Islamic entrepreneurship as a framework for MSME empowerment that supports the optimization of the Complete Systematic Land Registration (Pendaftaran Tanah Sistematis Lengkap (PTSL) Program in strengthening Islamic financial inclusion and promoting sustainable economic development in Indonesia. ABSTRAK Usaha Mikro, Kecil, dan Menengah (UMKM) merupakan pilar utama perekonomian Indonesia, namun masih menghadapi keterbatasan dalam memperoleh akses pembiayaan formal, khususnya melalui lembaga keuangan syariah. Salah satu faktor yang menghambat optimalisasi pembiayaan tersebut adalah belum dimanfaatkannya sertifikat tanah secara maksimal sebagai agunan yang memiliki kepastian hukum. Artikel konseptual ini bertujuan menganalisis peran sertifikat tanah dalam memperluas akses pembiayaan syariah bagi UMKM serta mengkaji kontribusinya terhadap penguatan Islamic entrepreneurship. Penelitian menggunakan metode studi pustaka (library research) dengan tahapan identifikasi, seleksi, analisis kritis, dan sintesis berbagai literatur yang berkaitan dengan ekonomi syariah, hukum pertanahan, pembiayaan syariah, dan kewirausahaan Islam. Hasil kajian menunjukkan bahwa sertifikat tanah berfungsi sebagai objek jaminan (rahn) yang sah menurut prinsip syariah dan hukum positif sehingga mampu meningkatkan tingkat kepercayaan lembaga keuangan syariah, memperluas peluang UMKM memperoleh pembiayaan, serta mendorong terbentuknya tata kelola usaha yang lebih amanah, transparan, dan bertanggung jawab. Selain itu, penelitian ini menegaskan bahwa integrasi legalitas aset, pembiayaan syariah, dan Islamic entrepreneurship menjadi landasan konseptual bagi penguatan inklusi keuangan syariah dan pemberdayaan UMKM. Kebaruan artikel ini terletak pada integrasi konseptual antara sertifikat tanah, pembiayaan syariah, dan Islamic entrepreneurship sebagai kerangka pemberdayaan UMKM yang mendukung optimalisasi Program Pendaftaran Tanah Sistematis Lengkap (PTSL) dalam memperkuat inklusi keuangan syariah dan pembangunan ekonomi berkelanjutan di Indonesia.